Protective effects of breastfeeding against acute respiratory tract infections and diarrhoea: Findings of a cohort study. (30th January 2017) - Raheem, Raheema Abdul; Binns, Colin W; Chih, Hui J
Abstract : Aim: The objective of this paper is to identify associations between breastfeeding and acute respiratory tract infections (ARTIs) and diarrhoea. Methods: A cohort of 458 mothers was recruited at the antenatal clinics at Indira Gandhi Memorial and Abdul Rahman Dhon Kaleyfaanu Hospitals. Mothers were interviewed 'face‐to‐face' at 36 weeks of gestation and at 1, 3 and 6 months after delivery. The questionnaires included demographic information about parents, infant feeding methods and breastfeeding duration. The number of episodes of ARTIs and diarrhoea was also recorded. Ethics approval was obtained from the National Research Committee of the Maldives and Curtin University Human Research Ethics Committee. Descriptive, univariate, logistic and survival analyses were used to assess the effects of breastfeeding on infant ARTIs and diarrhoea. Results: The partial, predominant and exclusive breastfeeding rates at 1 month were 98.9, 67.6 and 26.9%, respectively. The risk of acquiring ARTIs is significantly reduced when the infants were predominantly breastfed for 3 months (adjusted odds ratio (OR): 0.56, 95% of adjusted OR: 0.34–0.94) and 6 months (adjusted OR: 0.45, 95% of adjusted OR: 0.24–0.84). The risk of getting diarrhoea is significantly reduced even when the babies were partially breastfed for 6 months (adjusted OR): 0.31, 95% of adjusted OR: 0.11–0.90). Kaplan Meier curves demonstrated that the risk lowers with longer duration of breastfeeding. Conclusion: Breastfeeding need to be promoted because the risk of infant morbidity is negatively associated with the duration of breastfeeding.